Alpha-Ketoglutarate Alleviates Neuronal Apoptosis Induced by Central Insulin Resistance through Inhibiting S6K1 Phosphorylation after Subarachnoid Hemorrhage. (25th August 2022) - Ding, Peng-Fei; Zhu, Qi; Sheng, Bin; Yang, Heng; Xu, Hua-Jie; Tao, Tao; Peng, Zheng; Chen, Xiang-Xin; Li, Xiao-Jian; Zhou, Yan; Zhang, Hua-Sheng; Gao, Yong-Yue; et al.
Abstract : Neuronal apoptosis after subarachnoid hemorrhage (SAH) is believed to play an important role in early brain injury after SAH. The energy metabolism of neuron is closely related to its survival. The transient hyperglycemia caused by insulin resistance (IR) after SAH seriously affects the prognosis of patients. However, the specific mechanisms of IR after SAH are still not clear. Studies have shown that α -KG takes part in the regulation of IR and cell apoptosis. In this study, we aim to investigate whether α -KG can reduce IR after SAH, improve the disorder of neuronal glucose metabolism, alleviate neuronal apoptosis, and ultimately play a neuroprotective role in SAH-induced EBI. We first measured α -KG levels in the cerebrospinal fluid (CSF) of patients with SAH. Then, we established a SAH model through hemoglobin (Hb) stimulation with HT22 cells for further mechanism research. Furthermore, an in vivo SAH model in mice was established by endovascular perforation. Our results showed that α -KG levels in CSF significantly increased in SAH patients and could be used as a potential prognostic biomarker. In in vitro model of SAH, we found that α -KG not only inhibited IR-induced reduction of glucose uptake in neurons after SAH but also alleviated SAH-induced neuronal apoptosis. Mechanistically, we found that α -KG inhibits neuronal IR by inhibiting S6K1 activation after SAH. Moreover, neuronal apoptosis significantly increased when glucose uptake was reduced. Furthermore, our results demonstrated that α -KG could also alleviate neuronal apoptosis in vivo SAH model. In conclusion, our study suggests that α -KG alleviates apoptosis by inhibiting IR induced by S6K1 activation after SAH.